Research Cluster in Engineering Education and Human Resource Development - Vedhathiri, Thanikachalam (Journal of Engineering Education Transformations, 2025)
The Ministry of Human Resource Development envisaged a research cluster in engineering education in the 1980s under United Nation's Development Project in technician education development. Many initiatives have been taken to institutionalize research in engineering education by the Technical Teachers Training Institutes (now National Institutes of Technical Teachers Training and Research) in Bhopal, Chandigarh, Chennai, and Kolkata. These four institutes have grown into the Centers of Excellence in Engineering Education and assisted the project polytechnics, State Project Implementing Units, National Project Implementing Unit and World Bank. They offer part-time and full-time interdisciplinary Ph.D. programs in curriculum evaluation, improvement, instructional design, improvement of diploma, degree and postgraduate programs, educational administration, educational management, institutional development, human resource development and management.